Editorial - Teye, Prof. G. A. (UDS International Journal of Development, 2022)
The UDS International Journal of Development (UDSIJD) presents publications for Volume 9, Issue 1. This issue is coming out later in the year than usual and this is attributed to challenges and delays with the reviewing process, which we have worked tirelessly to resolve. Despite the challenges, the Journal continues to be a great channel of research. The UDSIJD is in the process of being indexed by the African Journals Online (AJOL) platform so as to enhance visibility of the publications. As an open access journal, UDSIJD is committed to ensuring immediate and full open access to its research publications across disciplines and therefore continue to encourage submissions from early career researchers. We strongly advice that authors pay critical attention to the journal’s guidelines before submission and also be patient with the review process as the editorial team are competent experts and these interferences are unnecessary. We would also like to acknowledge all who made time to review the articles published in this issue. Your sacrifice is deeply appreciated and we hope you would not hesitate to be of service as and when the need arises. The Editorial Team wishes to sincerely thank the University Management, authors, reviewers and staff of the Journal and all those who in diverse ways have supported in making this issue of the Journal a reality. The Editor-in-Chief Prof. G. A. Teye